Islam, Ethics and Psychological Self-control - Hamid Rafi’ee Honar (اخلاق وحیانی, 2013)
Everyone would admit that individuals have a set of ethical codes by the help of which they distinguish good deeds from bad deeds. Such ethical codes would condemn selfish, impulsive and shortsighted actions on the one hand, and reinforce actions that would lead to broader perspectives on the other. As a result of these sets of codes, people start making choices. The ability of making such choices is what is referred to as ‘self-control’. Nowadays, self-control is recognized in psychology as a capability that keeps an individual’s behavior within the boundaries of the accepted rules and criteria. However, it is possible for everyone to have experienced some failures, in some cases, based on his own idea of ethical codes. Therefore, the power of self-control needs assistance and help and the teachings of the religions can be rather effective in this regard. Apparently, according to the teachings of Islam, a wide variety of moral virtues arise from success in self-control. For instance, virtues such as discretion, dignity, patience, and above all ‘piety’ all originate from self-control. On the contrary, moral vices are considered to be a test for self-control in this regard. Thus, the present paper aims at investigating the capability of Islam in cultivating virtuous and ethical behavior in the people through reinforcing and promoting self-control factors. Through these studies we will realize that Islam pursues the reinforcement and promotion of self-control through five methods which are as follows: ‘offering clear standards’, ‘creating incentive for moral behavior’, ‘monitoring the individuals’ behavior’, ‘managing the indecent desires’, and ‘containing and regulating the emotions’.